HDAC3 increases HMGB3 expression to facilitate the immune escape of breast cancer cells via down-regulating microRNA-130a-3p. (June 2021) - Chen, Zonglin; Pei, Lei; Zhang, Danhua; Xu, Feng; Zhou, Enxiang; Chen, Xianyu
Abstract: Objective: Histone deacetylase 3 (HDAC3) has been reported to repress the expression of various genes by eliminating acetyl group from histone. The objective of this study was to discuss the effect of HDAC3/microRNA-130a-3p (miR-130a-3p)/high-mobility group box 3 (HMGB3) on immune escape of breast cancer. Methods: HDAC3, miR-130a-3p and HMGB3 expression in breast cancer tissues and cells were tested, and the correlation between HDAC3, miR-130a-3p and HMGB3 was analyzed. CD8, CD69 and programmed cell death protein 1 (PD-1) expression was detected. MDA-MB-231 cells were treated with relative plasmid of HDAC3 or miR-130a-3p to test cell viability, migration, epithelial-mesenchymal transition (EMT) and apoptosis in MDA-MB-231 cells. The cytotoxicity of CD8 + /CD69 + /PD-1 + T cells in MDA-MB-231 cells was tested, and CD8 + /CD69 + /PD-1 + T cell proliferation and apoptosis before and after co-culture with MDA-MB-231 cells were detected. Results: HDAC3 and HMGB3 expression were raised and miR-130a-3p expression was diminished in breast cancer tissues and cells. HDAC3 was negatively correlated with miR-130a-3p while miR-130a-3p was negatively correlated with HMGB3. Down-regulating HDAC3 or up-regulating miR-130a-3p restrained cell viability, migration, EMT and anti-CD8 + /CD69 + /PD-1 + T cytotoxicity and facilitated apoptosis of breast cancer cells. HDAC3 regulated HMGB3 by mediating miR-130a-3p expression. Down-regulating miR-130a-3p reversed the role of HDAC3 reduction on breast cancer cells. HDAC3 regulated CD8 + /CD69 + /PD-1 + T cell proliferation and apoptosis by mediating miR-130a-3p. Conclusion: This study provides evidence that HDAC3 increases HMGB3 expression to promote the immune escape of breast cancer cells via down-regulating miR-130a-3p.